The Effect of Internal Bank Aspects to Sharia Bank Performance with Financing Risk as Mediator - Lestari, Nimas Dewi; Qanita, Ariza; Suyuti, Mufit; Prajawati, Maretha Ika; Ningtyas, Mega Noerman (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to examine the factors that affect financing risk and its influence on the financial performance (profit) of Islamic banking in Indonesia. The study includes an overview of internal conditions including capital elements and bank operating costs. This study uses a quantitative method with a path analysis approach. The object of study is Islamic general banking in Indonesia which is registered with the Financial Services Authority (OJK) for the 2019-2023 period. The sampling technique uses the purposive sampling technique with a total sample of 9 Islamic commercial banks in Indonesia. The results of this study show that CAR has a significant effect on NPF, OER does not have a significant effect on NPF, directly CAR and NPF do not have a significant effect on ROA, directly OER has a significant effect on ROA, indirectly through NPF, CAR and OER do not have a significant effect on ROA. The results of this study conclude that Islamic public banks in Indonesia must be able to efficiently manage capital reserves and company operating costs. This aims to maintain the stability of banking performance and ensure that Islamic banks can mitigate the level of risk that occurs in banking operational activities.